Analisis Faktor-Faktor Yang Mempengaruhi Penyaluran Kredit (Studi Pada Bank Umum Konvensional Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2018) - Erwin Febriansyah; Ade Tiara Yulinda; Nensi Yuniarti (UNIVED Press, 2022)
The purpose of this study was to determine the effect of NPL, ROA, ROE, LDR on lending to conventional commercial banks listed on the Indonesian stock exchange. The population in this study is conventional commercial banks listed on the Indonesian stock exchange in the 2014-2018 period, namely 41 companies. The research sample was determined by a method based on criteria so that the number of samples was 20 companies. Data collection in this study was taken from the financial statements of each company. The analysis technique used was multiple linear regression and hypothesis testing f and t-statistics. In the results of the research partially ROE has a significant effect on lending. NPL, ROA and LDR have no significant effect on lending. Meanwhile, Simultaneously NPL, ROA, ROE, LDR have a significant effect on lending.